2021
DOI: 10.3390/su13105359
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perceptions of Commercial Insect-Based Feed for Sustainable Livestock Production in Kenya

Abstract: The utilization of insect-based feeds (IBF) as an alternative protein source is increasingly gaining momentum worldwide owing to recent concerns over the impact of food systems on the environment. However, its large-scale adoption will depend on farmers’ acceptance of its key qualities. This study evaluates farmer’s perceptions of commercial IBF products and assesses the factors that would influence its adoption. It employs principal component analysis (PCA) to develop perception indices that are subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For instance, Schouteten et al ( 2016 ) observed that increasing acceptance of insects as an alternative food group is mainly attributed to consumer awareness of the nutritional benefits associated with insects. Other recent studies have also shown that consumer knowledge, which informs awareness, influences willingness to consume insect-based foods, willingness to use insect-based feeds for livestock, and perceptions as a protein source (Piha et al 2018 ; Kim et al 2019 ; Okello et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Schouteten et al ( 2016 ) observed that increasing acceptance of insects as an alternative food group is mainly attributed to consumer awareness of the nutritional benefits associated with insects. Other recent studies have also shown that consumer knowledge, which informs awareness, influences willingness to consume insect-based foods, willingness to use insect-based feeds for livestock, and perceptions as a protein source (Piha et al 2018 ; Kim et al 2019 ; Okello et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The similarity in these parameters for chicken fed on diets where fishmeal was replaced with BGM confirms similar nutritional benefits. According to Okello et al (2021), farmers are willing to accept the incorporation of IBF as there is no longer credible information indicating the benefits of a given insect meal. The current study has found utilizing BGM in chicken diets is as good as using conventional fishmeal.…”
Section: Effects Of Diets With B Germanica Meal (Bgm) On Total Weight...mentioning
confidence: 99%
“…Further, the retained factors cumulatively explained 37% of the variation (Table A1). Although only five statements had factor loadings above the recommended threshold of 0.5 as indicated by Okello, et al (2021), all the 7 statements were used to calculate the KP index.…”
Section: Severity Symptoms and Knowledge Of Fruit Fly Infestation And...mentioning
confidence: 99%